Rheology of peach pulp as affected by temperature and added granular activated carbon - Arslanoglu, FN; Kar, F; Arslan, N (Springer India, 2005)
The flow properties of peach pulp-granular activated carbon mixtures were determined over a range of temperatures (15-40 degrees C), granular activated carbon concentrations (0.5-5 kg/m(3)) and rotational speed (5-60 rpm) by using a rotational viscometer. The flow properties of peach pulp-granular activated carbon mixtures were suitably described by power-law model and exhibited a pseudoplastic behaviour. The flow behaviour index and the consistency coefficient of peach pulp-granular activated carbon mixtures were in the ranges of 0.328-0.512 and 2.17-6.18 Pas(n), respectively. Both the consistency coefficient and the flow behaviour index decreased with temperature. The consistency coefficient increased with granular activated carbon concentration, while no harmonious variation observed at the flow behaviour index values with increase in concentration. The apparent viscosity decreased with increasing temperature and shear rate, implying that molasses with or without added activated carbon behaved as shear thinning. The mathematical models to predict the apparent viscosity of peach pulp-granular activated carbon mixtures as a function of activated carbon concentration, temperature and shear rate were developed. The suitability of the models relating the apparent viscosity was judged by using statistical parameters such as MPE, RMSE, EF and chi(2). The predicted results agreed reasonably well with experimental data.
Keywords: peach pulp; granular activated carbon; rheology; apparent viscosity